Both alcohol and halogenated solvents soluble soft-metal sensor functional phthalocyanines: synthesis, electrochemistry, spectroelectrochemistry - (:unkn) unknown (WORLD SCI PUBL CO INC, 2009)
In this study, we report a novel both alcohol and haloganated solvent soluble selective ionophore functional ligand and its beta-substituted 2(3),9(10),16(17),23(24)-tetrakis(1-hydroxyhexan-3-ylthio)- phthalocyanines, M{Pc[S-CH(CH(2)CH(2)CH(3))(CH(2)CH(2)OH)](4)}, (Pc: Phthalocyanine) (M = Zn, Cu, Co), where -OH indicates peripheral functionality. Pcs exhibiting both hydrophobic and hydrophilic character were characterized spectroscopically (FT-IR, (1)H and (13)C NMR, MS (MALDI-TOF) and UV-vis), electrochemically and spectroelectrochemically. The complexes were soluble in both polar solvents, such as MeOH and EtOH, and non-polar solvents such as CHCl(3), CH(2)Cl(2), benzene, toluene, and even hexane. Absorption spectral changes of the functional MPcs during addition of Ag(I) and Pd(II) soft-metal ions are evaluated by monomer-oligomer and even polymer formations technique and monitored for in situ monitoring technique in the UV-vis spectroscopy. The binding process results in considerable blue-shift in the absorption spectra of MPcs. According to continuous variation method, the ligand: metal ratio was found ca. 1:1 and 1.5:1 for total concentration of 1.0 x 10(-5) M and 7.5 x 10(-5) M, respectively. Their electrochemical and spectroelectrochemical studies show that the complexes exhibited stable monoanionic M{Pc[S-CH(CH(2)CH(2)CH(3))(CH(2)CH(2)OH)](4)}(1-), dianionic M{Pc[S-CH(CH(2)CH(2)CH(3)) (CH(2)CH(2)OH)](4)}(2-) and monocationic M{Pc[S-CH(CH(2)CH(2)CH(3))(CH(2)CH(2)OH)](4)}(1+) species during reduction and oxidation processes.
Keywords: phthalocyanine; silver; palladium; metal sensor; job method; MALDI-TOF; electrochemistry; spectroelectrochemistry; ION BINDING; SUBSTITUTED COBALT; COMPLEXES; REDUCTION; METALLOPHTHALOCYANINES; PORPHYRAZINES; SPECTROSCOPY; OXIDATION; OXYGEN; FILMS